The THE CHALLENGES OF THE CAMINHO DA ESCOLA PROGRAM: A PERSPECTIVE ON SÃO BORJA: A PERSPECTIVE ON SÃO BORJA (Interdisciplinary Studies Journal, 2024)
: This article aims to discuss rural education and the Caminho da Escola Program, a federal public policy that helps ensure access to education. It is important to emphasize that this is an initial theoretical foundation that will lead to further research. The scope of the study is focused on Olinto Dornelles School, which is part of the municipal education network of São Borja - RS. Throughout the article, key concepts are outlined to understand the topic: initially, the term public policies is defined, with an emphasis on educational policies. Then, a synthesis is presented on rural education, its trajectories, and current challenges. Finally, the Caminho da Escola Program is discussed, including its implementation and functioning, as well as how it fits into the scope of this research, specifically its implementation in the municipality of São Borja. In this sense, this is a bibliographic review that uses qualitative methodology to understand the nuances of the public policy studied, as well os its target audience and expectations. The proposed intention is to bring an initial debate, considering that the research is still ongoing, addressing the main aspects of the program, its implementation process, improvement points, and challenges, considering the reality of the target school of the study.
Keywords: Public Policies; Caminho da Escola; Education; Rural School.